THE EFFECT OF PROFITABILITY ON CAPITAL STRUCTURE IN THE MANUFACTURING COMPANIES SUBSECTOR METALS LISTED IN INDONESIA STOCK EXCHANGE (IDX) YEAR 2011-2013 - I.P, Amelia Fitriani (Universitas Pendidikan Indonesia, 2015)
This study aims to determine the effect of profitability on the capital structure of the Manufacturing Companies subsector Metals are Listed in Indonesia Stock Exchange in 2011-2013, in this study profitability is measured using the Return on Assets (ROA), and capital structure were measured using Debt to Equity Ratio (DER ). The method used is descriptive method verification. The data collection techniques used is a method of documentation. Data in the form of financial statements obtained from the official website of Indonesia Stock Exchange 2011-2013. With a total sample of 10 Metals Companies listed on the BEI for three periods of study in order to get 30 data observan. Statistical analysis used is simple linear regression analysis, which is preceded by a test for normality and linearity as a prerequisite regression test then testing the significance of regression (F test) and regression coefficient significance test (t test). Based on the results of data processing, the known value of ROA decreased, while DER increased. Based on the statistical test result that profitability does not affect the capital structure. Keywords: Profitability, Capital Structure.